ArchEvolve: A Collaborative and Interactive Search-Based Framework with Preference Learning for Optimizing Software Architectures - Ayobami E. Mesioye; Adesola M. Falade; Kayode E. Akinola (Universitas Dian Nuswantoro, 2025)
The use of Search-Based Software Engineering (SBSE) for optimizing software architecture has evolved from fully automated to interactive approaches, integrating human expertise. However, current interactive tools face limitations: they typically support only single decision-makers, confine architects to passive roles, and induce significant cognitive fatigue from repetitive evaluations. These issues disconnect them from modern, team-based software development, where collaboration and consensus are crucial. To address these shortcomings, we propose